PENGAWASAN DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI KEPULAUAN RIAU TERHADAP PEREDARAN MAINAN ANAK YANG TIDAK MEMPUNYAI STANDAR NASIONAL INDONESIA DI KOTA TANJUNGPINANG TAHUN 2018 - Faruq Irfan; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The function of the government is to provide guidance and supervision of children's toy products, in this case the government is responsible for the implementation of consumer protection which ensures that the rights of consumers and business actors are obtained as well as the implementation of the obligations of consumers and business actors. Based on the function of the government as a supervisor carried out by the Industry and Trade Office of the Riau Islands Province as a supervisor in the field of SNI for children's toys, it is necessary to create a system that is able to provide protection to the community. In this case, the Government has responsibility for the security and safety of its citizens who are required to go directly to monitor the nets in order to avoid losses to the community. The purpose of this study was to determine the supervision of the circulation of children's toys without Indonesian National Standards carried out by the government in this case the Industry and Trade Office of the Riau Islands Province and the inhibiting factors for the Supervision of the Industry and Trade Office of the Riau Islands Province against the circulation of children's toys that do not have Indonesian national standards in Indonesia. Tanjungpinang City in 2018. This study uses a qualitative approach with a descriptive method. The results of this study are that there are still some business actors who sell children's toys without Indonesian National Standards, this shows the weak supervision of the Industry and Trade Office of the Riau Islands Province due to the lack of supervisory officers for circulating goods and services and the low capacity of national supporting institutions and the lack of frequency of supervision of toys. non-sni child. Keywords: Supervision, Cyclical Children Toys, Indonesia